The effect of saddle height on pedalling mechanical efficiency during cycling - Peleg, S.; Ravina, O.; Steinberg, N. (International Journal of Performance Analysis in Sport, 2025)
Background: Mechanical pedaling efficiency can be measured via vertical force applied to the crank during cycling. This research physically evaluated the influence of three saddle heights, measured as 25°, 30° and 35° knee-flexion angles during static position, on the mechanical pedalling efficiency of competitive cyclists. Methods: The study included 30 young male competitive-level cyclists. Measurements were taken using their personal bicycles mounted onto a Wahoo KICKR 4 trainer model; pedals were replaced with Garmin® Vector pedals, data were transmitted to a computer via a Garmin Fenix® 6 watch. Following a 5 min cycling warmup, the participants completed three 2 min sessions at 3 watt/kg and 90-100 rpm, one session for each saddle height, while maintaining a relaxed upper body position. To assess total mechanical pedalling efficiency, a one-way ANOVA was conducted on the three kinetic indices. Findings and Interpretation: A saddle height of a 25° knee-flexion angle statically measured was found to be most mechanically effective among competitive cyclists, regardless of height, BMI and flexibility. We recommend adding this kinetic tool to kinematic tools (joint angles) and subjective report in bike fitting and in coaching.